PENGARUH CELEBRITY ENDORSER DAN BRAND IMAGE TERHADAP MINAT BELI KONSUMEN SKINCARE MS GLOW (Studi Pada Konsumen MS Glow di Jawa Timur): THE EFFECT OF CELEBRITY ENDORSER AND BRAND IMAGE ON CONSUMER PURCHASE INTEREST OF SKINCARE MS GLOW (Study on MS Glow Consumers in East Java) - Niken Puspita Sari; Tri Sudarwanto (Universitas Sains dan Teknologi Komputer, 2022)
MS Glow is one of the beauty care brands in Indonesia, which this local brand is very popular because it offers benefits that can brighten the skin. The company's strategy is to take advantage of promotions by collaborating with Celebrity Endorsers. This research was motivated by the phenomenon of the extremely high of MS Glow products sales which caused MS Glow consumers to burst amid intense competition in the cosmetics industry in Indonesia and the presence of many new cosmetic brands emerging. This study aims to analyze the influence of celebrity endorsers and brand image simultaneously on consumers' buying interest in MS Glow products. The population in this study is MS Glow consumers in East Java who have used MS Glow products at least three times and have witnessed celebrity endorsers campaigning for MS Glow products. The sampling method used is non-probability sampling and purposive sampling is used data collection. The data were collected using a questionnaire which a sample of 100 respondents was taken. The type of research in this research is descriptive quantitative research using multiple linear regression analysis, coefficient of determination, partial test (T Test), and simultaneous test (Test F). The results in this study show that the celebrity endorser variable (X1) and the brand image variable (X2) partially (T Test) have a positive and significant influence on consumers' buying interest, while simultaneously (Test F) the celebrity endorser (X1) and brand image (X2) variables have a positive and significant influence on consumers' buying interest (Y). With R-Square Adjusted produced as much as 55.2% and the remaining 44.8% influenced by other variables.